Do Loan-To-Value and Debt-To-Income Limits Work? : Evidence From Korea - Igan, Deniz (IMF Working Papers; Working Paper ;, 2011)
With another real estate boom-bust bringing woes to the world economy, a quest for a better policy toolkit to deal with these boom-busts has begun. Macroprudential measures could be in such a toolkit. Yet, we know very little about their impact. This paper takes a step to fill this gap by analyzing the Korean experience with these measures. We find that loan-to-value and debt-to-income limits are associated with a decline in house price appreciation and transaction activity. Furthermore, the limits alter expectations, which play a key role in bubble dynamics.